PENGARUH KEPEMIMPINAN, MOTIVASI, KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA KARYAWAN PADA KARYAWAN PT.SMARTFREN,Tbk DI SURABAYA - CIPTODIHARDJO, IRAWAN (Universitas Katolik Widya Mandala Surabaya, 2013)
The purpose of this study, which is to be achieved is to test and analyze the influence of leadership, motivation, job satisfaction and organizational commitment to employee performance. The benefits gained from this research is to provide feedback or additional info meant for organizations, companies and further research on leadership, motivation, job satisfaction, organizational commitment and employee performance as a reference for future studies. The variables of this study consists of eksogen and endogen variables. Eksogen variables consist of leadership, motivation and job satisfaction. As for the endogen variables consist of organizational commitment and employee performance. Analytical technique used is Structural Equation Modelling (SEM) with AMOS.The findings in this study that the leadership on organizational commitment, job satisfaction on organizational commitment and organizational commitment on employee performance is not significantly affected. While the motivation for organizational commitment, leadership on employee performance, motivation on employee performance, and job satisfaction on the performance is significantly affected.